Risk factors for cognitive decline in older Chinese adults: the impact of social activity on the relationship between hearing, functional mobility, and cognition - Hao Wang; Dan Chen; Daling Hu; Fangyuan Tian; Meifen Dai; Shuangyan Zhang; Liyu Jin (Frontiers Media S.A., 2024)
ObjectiveHearing and functional mobility impairments are recognized as risk factors for cognitive decline in older adults, yet the causal relationship underlying these associations is not well-understood. This study aims to explore whether engagement in social activities mediates the link between hearing or functional mobility impairment and cognitive decline.MethodsThis cross-sectional study was carried out in two cities in Jiangsu Province, Eastern China. Participants self-reported hearing impairment and social activity engagement, whereas functional mobility impairment was assessed using the Timed Up and Go Test (TUGT). Cognitive function was evaluated through the Modified Mini-Mental State Examination (MMSE). Logistic regression analysis explored factors influencing cognitive function, and mediation analysis was conducted to examine the relationship between hearing or functional mobility impairment and cognitive decline.ResultsThe study included 10,217 adults aged 60 and above. Among them, 19.35% reported hearing impairment, while 40.86% failed the Timed Up and Go Test (TUGT). The Modified Mini-Mental State Examination (MMSE) indicated a 30.40% prevalence of cognitive decline. Logistic regression analysis identified significant associations of cognitive function with factors such as gender, age, education level, residency, living arrangement, hyperlipidemia, cerebrovascular disease, alcohol consumption, smoking, Activities of Daily Living (ADLs), Instrumental Activities of Daily Living (IADLs), social activity, hearing, and functional mobility (p < 0.01). Mediation analysis, after adjusting for confounders, showed that social activity engagement partially mediated the impact of functional mobility impairment on cognitive decline (indirect effect: −0.0947, 95% Bootstrapped CI: −0.1228, −0.0695; proportion of total effect: 11.635%, p < 0.01). However, no mediation effect was observed in the relationship between self-reported hearing impairment and cognitive decline.ConclusionThis study revealed that social activity engagement plays a mediating role in the relationship between functional mobility and cognitive function, but it does not significantly influence the relationship between self-reported hearing impairment and cognitive decline. These findings suggest that social activity engagement could be a crucial factor in preventing cognitive deterioration among older adults with functional mobility impairments.